A W with fast photochromic properties 18 O 49 Nanomaterials and their preparation methods and applications

By doping metal elements into the W18O49 lattice, the problem of slow response speed and low color change in W18O49 material is solved, and the rapid photochromic effect is achieved, expanding its application in the fields of erotic paper, smart windows, etc.

CN115161005BActive Publication Date: 2025-03-18WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210892570.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-03-18
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

The existing W18O49 materials have slow response speed and low discoloration in photochromicity, which limits their application in the fields of erotic paper, smart windows, etc.

Method used

By doping metal elements, such as titanium, into the W18O49 lattice, its band gap width and defect concentration are adjusted, thereby improving the response speed and colorimetric degree of the photochromic material.

Benefits of technology

The photochromic response speed and color change of W18O49-based nanomaterials have been significantly improved, allowing them to quickly change their colors under ultraviolet light, and are suitable for applications such as rewritable paper and smart windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115161005B_ABST
    Figure CN115161005B_ABST
Patent Text Reader

Abstract

The present invention relates to a W having rapid photochromic properties. 18 O 49 Based nanomaterials and preparation methods and applications thereof, the W having rapid photochromic properties 18 O 49 The base nanomaterial is W doped with metal elements 18 O 49 , the metal element is one of titanium, copper, zirconium, vanadium, zinc, aluminum, and molybdenum, and the metal element is 18 O 49 The molar ratio of tungsten in the present invention is 0.05-0.40:1. 18 O 49 The based nanomaterials can change color under ultraviolet light, and the color difference before and after the color change is large. They are highly sensitive to ultraviolet light and have a fast response speed. The color maintenance time is greater than 12 hours at room temperature. They have application prospects in erasable paper, anti-counterfeiting materials, smart windows, thermal insulation coatings, decorative materials, packaging materials and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of color-changing fluorescent materials, and in particular relates to a W having rapid photochromic properties. 18 O 49 Based nanomaterials and their preparation methods and applications. Background Art

[0002] Photochromism refers to the change in the molecular structure of certain compounds under the action of light of a certain wavelength and intensity, which leads to a corresponding change in its light absorption peak, that is, color, and this change is generally reversible. Due to its important applications in wearable UV sensors, rewritable paper, and smart windows, people are increasingly interested in photochromic materials. Many photochromic organic molecules, such as azobenzene, spiropyran, and naphthone, exhibit fast and efficient color switching. However, the photoinduced degradation of these organic molecules in complex synthesis processes and toxic synthetic precursors is severe and uncontrollable.

[0003] The inorganic photochromic materials that are most studied at present are WO3, MoO3, TiO2, VO2, etc., and W with oxygen defects 18 O 49 However, there are few reports. 18 O 49 As a tungsten oxide with oxygen vacancies, it has a narrower bandgap than WO3 (2.7-3.5 eV) and can be used as a photochromic material with faster response. 18 O 49 Since the material itself is blue, the color change is low and the response speed is slow, which greatly limits its application. 18 O 49 After being modified by doping with metal elements, its color change degree and response speed can be significantly improved, and it has great application prospects in erasable paper, photochromic smart windows, thermal insulation coatings, anti-counterfeiting of valuables, and decorative and protective packaging materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a W having a fast photochromic property in view of the above-mentioned deficiencies in the prior art. 18 O 49 Based nanomaterials and their preparation methods and applications.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] Providing a W with fast photochromic properties 18 O 49 Based nanomaterials, the W 18 O 49 The base nanomaterial is W doped with metal elements18 O 49 , the metal element is one of titanium, copper, zirconium, vanadium, zinc, aluminum, and molybdenum, and the metal element is 18 O 49 The molar ratio of tungsten in China is 0.05-0.40:1.

[0007] According to the above scheme, the W having fast photochromic properties 18 O 49 The base nanomaterial is a nanosphere obtained by agglomerating nanoparticles with a particle size of 10 to 100 nm, and the average particle size is 400 to 1000 nm.

[0008] The present invention also includes the W having fast photochromic properties 18 O 49 The preparation method of the nano-based material comprises the following specific steps:

[0009] 1) Dissolve the tungsten source in ethanol and stir until it turns yellow and transparent to obtain a precursor solution;

[0010] 2) adding a soluble salt of the doped metal element to the precursor solution obtained in step 1), stirring evenly, and then transferring to a reactor for solvothermal reaction, filtering out a solid product after the reaction is completed, washing and drying the solid product, and then grinding and sieving it, and finally heat-treating the obtained solid product to obtain W having rapid photochromic properties. 18 O 49 Based nanomaterials.

[0011] According to the above scheme, the tungsten source in step 1) is one of tungsten hexachloride (WCl6), sodium tungstate (Na2WO4), sodium tungstate dihydrate (Na2WO4·2H2O), and tungsten hexacarbonyl (W(CO)6).

[0012] According to the above scheme, the concentration of tungsten ions in the precursor solution in step 1) is 0.005-0.030 mol / L.

[0013] According to the above scheme, the soluble salt of the doped metal element in step 2) is a soluble salt of one of titanium, copper, zirconium, vanadium, zinc, aluminum, and molybdenum, such as chloride or nitrate.

[0014] According to the above scheme, the molar ratio of the metal element in the soluble salt of the metal element doped in step 2) to the tungsten element in the tungsten source is 0.05-0.40:1.

[0015] According to the above scheme, the solvent thermal reaction conditions of step 2) are: reacting at 180-220° C. for 12-24 hours.

[0016] According to the above scheme, the heat treatment process conditions in step 2) are: heating at 120-200°C for 1-2 hours. The purpose is to partially oxidize the sample, changing the color from blue to lighter yellow or pale white, so as to facilitate the observation of color difference changes.

[0017] The present invention also includes the W having fast photochromic properties 18 O 49 Application of nanomaterials in erasable paper, anti-counterfeiting materials, smart windows, thermal insulation coatings, decorative materials, and packaging materials.

[0018] The present invention dopes appropriate metal elements into W 18 O 49 Nanomaterials doped with metal elements are synthesized in the lattice. Taking titanium as an example, Ti with a smaller ionic radius 4+ Replacement W 6+ and W 5+ Lattice sites can effectively increase W 18 O 49 The defect concentration in the crystal reduces the bandgap width, causing the absorption edge to redshift. The proper increase in defect concentration can provide more binding sites for photogenerated electrons, making Ti-doped W 18 O 49 The nanomaterial changes from light yellow to blue faster. 18 O 49 lattice, improving W 18 O 49 The color-changing ability of nanomaterials improves their photochromic sensitivity and response speed.

[0019] The beneficial effects of the present invention are: 1. The W 18 O 49 The nanomaterial can change color under ultraviolet light, and the color difference before and after the color change is large. It has high sensitivity to ultraviolet light and fast response speed. The color retention time is greater than 12 hours under room temperature. 18 O 49 The erasable paper prepared by the W-based nanomaterial can be repeatedly erased more than 10 times. 18 O 49 The photochromic film prepared from the nanomaterial can change color repeatedly for more than 10 times, and has application prospects in the fields of erasable paper, anti-counterfeiting materials, smart windows, thermal insulation coatings, decorative materials, packaging materials, etc. 2. The preparation method of the present invention has simple steps, mild conditions, easy-to-obtain raw materials, low cost, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 W prepared in Comparative Example 1 of the present invention 18 O49 SEM images of nanomaterials;

[0021] Figure 2 W prepared in Comparative Example 1 18 O 49 XRD patterns of samples before and after pyrolysis of nanomaterials;

[0022] Figure 3 W prepared in Comparative Example 1 18 O 49 The color difference curve of nanomaterials after being irradiated with ultraviolet light for different time periods;

[0023] Figure 4 W prepared in Comparative Example 1 18 O 49 The change of color difference of nanomaterials in 150℃ environment after irradiation with UV light for 5 seconds;

[0024] Figure 5 The titanium-doped W prepared in Example 1 18 O 49 XRD patterns of samples before and after pyrolysis of nanomaterials;

[0025] Figure 6 The titanium-doped W prepared in Example 1 18 O 49 The color difference curve of nanomaterials after being irradiated with ultraviolet light for different time periods;

[0026] Figure 7 The titanium-doped W prepared in Example 1 18 O 49 The change of color difference of nanomaterials at 150℃ after 5 minutes of UV light irradiation;

[0027] Figure 8 The titanium-doped W prepared in Example 2 18 O 49 SEM images of nanomaterials;

[0028] Fig. 9 The titanium-doped W prepared in Example 2 18 O 49 XRD patterns of samples before and after pyrolysis of nanomaterials;

[0029] Fig.10 The titanium-doped W prepared in Example 2 18 O 49 XPS spectra of nanomaterials;

[0030] Fig.11 The titanium-doped W prepared in Example 2 18 O 49The color difference curve of nanomaterials after being irradiated with ultraviolet light for different time periods;

[0031] Fig.12 The titanium-doped W prepared in Example 2 18 O 49 The change in color difference of nanomaterials at 150°C after being irradiated with ultraviolet light for 5 minutes. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0033] Comparative Example 1

[0034] Undoped W 18 O 49 Nanomaterials, the specific preparation method is as follows:

[0035] Weigh 0.4759 g of tungsten hexachloride and 40 mL of anhydrous ethanol into a 100 mL beaker, stir magnetically until the color becomes transparent orange-yellow, transfer to a reactor with a volume of 100 mL, place the reactor in an oven at 180 ° C for 12 h, centrifuge the blue product obtained from the above reaction, wash it with deionized water and ethanol three times in sequence, and finally vacuum dry it at 60 ° C for 12 h. Grind the dried sample until it can pass through a 400-mesh sieve, and heat treat it at 150 ° C for 1.5 h to obtain the final sample.

[0036] Figure 1 W prepared in this comparative example 18 O 49 SEM images of nanomaterials show that undoped W 18 O 49 The nanomaterial is a sea urchin-shaped sphere formed by the aggregation of nanowires. The diameter of the nanowires is about ten nanometers and the length is hundreds of nanometers. The diameter of the sea urchin-shaped sphere is 600 to 1000 nm.

[0037] Figure 2 W prepared in this comparative example 18 O 49 XRD diagram of the nanomaterial samples before and after heat treatment. It can be seen from the figure that both samples have W at 2θ=23.2° and 2θ=47.6° 18 O 49 The characteristic absorption peaks correspond to the (010) and (020) crystal planes, respectively, which correspond to the standard card 71-2450, indicating that heat treatment can change the color of the sample from blue to light yellow or light white, so that there is a greater color contrast after ultraviolet light irradiation, which is convenient for observing the color difference change. Heat treatment does not change its phase structure. The samples before and after heat treatment are all monoclinic W 18 O49 , good stability.

[0038] The WF30 precision colorimeter prepared by Shenzhen Weifu Optoelectronics Technology Co., Ltd. was used to test the W prepared in this comparative example. 18 O 49 The photochromic properties of nanomaterials are measured by measuring the color difference of samples under different irradiation times of ultraviolet light with an emission wavelength of 365nm and a power of 5W. Figure 3 W prepared in this comparative example 18 O 49 The color difference curve of nanomaterials after being irradiated with ultraviolet light for different time periods. It can be seen from the figure that W 18 O 49 The color difference of the nanomaterial is about 10 after being irradiated with ultraviolet light for 5 minutes.

[0039] Figure 4 W prepared in this comparative example 18 O 49 The color difference of the nanomaterial was changed within 10 minutes after being irradiated with ultraviolet light for 5 minutes and then placed in a 150°C oven. It can be seen from the figure that the color difference decreased fastest within 2 minutes, and as time increased, the color difference gradually decreased. 18 O 49 After the nanomaterial was placed for 10 minutes, the color difference decreased by about 4.

[0040] Example 1

[0041] A W with fast photochromic properties 18 O 49 Based nanomaterials, the specific preparation method is as follows:

[0042] Weigh 0.4759g of tungsten hexachloride and 40mL of anhydrous ethanol into a 100mL beaker, stir magnetically until the color turns transparent orange-yellow, then add 13.2μL of titanium tetrachloride (atomic molar ratio W:Ti=1:0.10), stir evenly, transfer to a reactor with a volume of 100mL, place the reactor in an oven at 180℃ for 12h, centrifuge the blue product obtained by the above reaction, wash it with deionized water and ethanol three times in sequence, and finally vacuum dry it at 60℃ for 12h, grind the dried sample until it can pass through a 400-mesh sieve, and heat treat it at 150℃ for 1.5h to obtain a light yellow sample (denoted as W 18 O 49 :0.10Ti).

[0043] Figure 5 The titanium-doped W prepared in this example 18 O 49 XRD patterns of nanomaterial samples before and after heat treatment. Doping did not change W18 O 49 phase, but the half-peak width of the (010) peak increases. According to the Scherrer formula, W 18 O 49 : The grain size of 0.10Ti is smaller than that of W in Comparative Example 1 18 O 49 The crystallinity of W in Comparative Example 1 is lower than that of W in Comparative Example 1. 18 O 49 The crystallinity of W 18 O 49 defects.

[0044] The color difference of the sample in this example was measured under different irradiation times of ultraviolet light with an emission wavelength of 365nm and a power of 5W. Figure 6 The titanium-doped W prepared in this example 18 O 49 From the color difference change curve of the nanomaterial after being irradiated with ultraviolet light for different times, it can be seen that the color difference of the nanomaterial can reach more than 5 when irradiated for 5s (the International Commission on Illumination CIE stipulates in CIE1931-RGB that ΔC>2 means that there is a significant difference between the two colors), the color difference reaches saturation at about 2min of irradiation time, and the color difference reaches 14 after 5min of ultraviolet light irradiation.

[0045] Figure 7 The titanium-doped W prepared in this example 18 O 49 The color difference of the nanomaterial was changed within 10 minutes after being irradiated with ultraviolet light for 5 minutes and then placed in a 150°C oven. It can be seen from the figure that the color difference decreased fastest within 2 minutes, and as time increased, the color difference gradually decreased. The titanium-doped W prepared in this embodiment 18 O 49 After the nanomaterial was placed for 10 minutes, the color difference was reduced to about 2.

[0046] Example 2

[0047] A W with fast photochromic properties 18 O 49 Based nanomaterials, the specific preparation method is as follows:

[0048] Weigh 0.4759g of tungsten hexachloride and 40mL of anhydrous ethanol into a 100mL beaker, stir magnetically until the color turns transparent orange-yellow, then add 33.0μL of titanium tetrachloride (atomic molar ratio W:Ti=1:0.25), stir evenly, transfer to a reactor with a volume of 100mL, place the reactor in an oven at 180℃ for 12h, centrifuge the blue product obtained by the above reaction, wash it with deionized water and ethanol three times in sequence, and finally vacuum dry it at 60℃ for 12h, grind the dried sample until it can pass through a 400-mesh sieve, and heat treat it at 150℃ for 1.5h to obtain a light yellow sample (denoted as W 18 O 49 :0.25Ti).

[0049] Figure 8 The titanium-doped W prepared in this example 18 O 49 The SEM image of the nanomaterial shows that the titanium-doped W 18 O 49 Nanomaterials are nanospheres formed by the aggregation of nanoparticles of about 20 to 60 nm, and the diameter of the nanospheres is 400 to 800 nm.

[0050] Fig. 9 The titanium-doped W prepared in this example 18 O 49 XRD patterns of nanomaterial samples before and after heat treatment. Doping did not change W 18 O 49 phase, but the half-peak width of the (010) peak increases, which is wider than that of the sample in Example 1. According to the Scherrer formula, W 18 O 49 : The grain size of 0.25Ti is smaller than that of W in Comparative Example 1 18 O 49 The grain size is also smaller than W 18 O 49 :0.10Ti grains, and the peak intensity of the (010) peak continues to weaken, indicating that the crystallinity is lower than that of W in Comparative Example 1. 18 O 49 The crystallinity is also lower than that of W 18 O 49 :0.10Ti crystallinity. It can be inferred that titanium doping increases W 18 O 49 defects, and with the increase of doping amount, the grain size gradually decreases and the crystallinity gradually decreases.

[0051] Fig.10 The titanium-doped W prepared in this example 18 O 49The XPS spectrum of the nanomaterial shows a Ti 2p orbital peak at a binding energy of 450-470 eV, indicating that titanium has successfully entered the W 18 O 49 in the crystal lattice.

[0052] The color difference of the sample in this example was measured under different irradiation times of ultraviolet light with an emission wavelength of 365nm and a power of 5W. Fig.11 The titanium-doped W prepared in this example 18 O 49 The color difference curve of the nanomaterial after being irradiated with ultraviolet light for different time periods shows that the color difference of the nanomaterial can reach more than 5 after irradiation for 5 seconds, the color difference reaches saturation after irradiation for about 2 minutes, and the color difference reaches 16 after irradiation with ultraviolet light for 5 minutes. Figure 3 , Figure 6 and Fig.11 This indicates that titanium doping can increase W 18 O 49 of color difference.

[0053] Fig.12 The titanium-doped W prepared in this example 18 O 49 The color difference of the nanomaterial after being irradiated with UV light for 5 minutes and then placed in a 150°C oven for 10 minutes is shown in the figure. It can be seen from the figure that the titanium-doped W prepared in this embodiment 18 O 49 The color difference of the nanomaterial quickly decreased to about 2 within 2 minutes, indicating that the material has a fast color change response speed.

Claims

1. A W with fast photochromic properties 18 O 49 Based nanomaterial, characterized in that The W 18 O 49 The base nanomaterial is W doped with metal elements 18 O 49 , the metal element is titanium, and the metal element and W 18 O 49 The molar ratio of tungsten in China is 0.05-0.25:1; The specific steps of its preparation method are as follows: 1) Dissolve the tungsten source in ethanol and stir until it turns yellow and transparent to obtain a precursor solution; 2) adding a soluble salt of a doped metal element to the precursor solution obtained in step 1), wherein the soluble salt of the doped metal element is a soluble salt of titanium, and the molar ratio of the metal element in the soluble salt of the doped metal element to the tungsten element in the tungsten source is 0.05-0.25:1, stirring evenly, and then transferring to a reactor for a solvent thermal reaction, and the solvent thermal reaction conditions are: reacting at 180-220° C. for 12-24 hours, filtering out a solid product after the reaction is completed, washing the solid product, drying it, grinding it, and sieving it, and finally heat treating the obtained solid product to obtain W having rapid photochromic properties. 18 O 49 Based on nanomaterials, the heat treatment process conditions are: heating at 120-200°C for 1-2h.

2. The W having fast photochromic properties according to claim 1 18 O 49 Based nanomaterial, characterized in that The W having fast photochromic properties 18 O 49 The base nanomaterial is a nanosphere obtained by agglomerating nanoparticles with a particle size of 10 to 100 nm, and the average particle size is 400 to 1000 nm.

3. A W having fast photochromic properties as claimed in claim 1 or 2 18 O 49 The method for preparing a nano-based material is characterized in that: The specific steps are as follows: 1) Dissolve the tungsten source in ethanol and stir until it turns yellow and transparent to obtain a precursor solution; 2) adding a soluble salt of a doped metal element to the precursor solution obtained in step 1), wherein the soluble salt of the doped metal element is a soluble salt of titanium, and the molar ratio of the metal element in the soluble salt of the doped metal element to the tungsten element in the tungsten source is 0.05-0.25:1, stirring evenly, and then transferring to a reactor for a solvent thermal reaction, and the solvent thermal reaction conditions are: reacting at 180-220° C. for 12-24 hours, filtering out a solid product after the reaction is completed, washing the solid product, drying it, grinding it, and sieving it, and finally heat treating the obtained solid product to obtain W having rapid photochromic properties. 18 O 49 Based on nanomaterials, the heat treatment process conditions are: heating at 120-200°C for 1-2h.

4. The W having fast photochromic properties according to claim 3 18 O 49 The method for preparing a nano-based material is characterized in that: In step 1), the tungsten source is one of tungsten hexachloride, sodium tungstate, sodium tungstate dihydrate, and tungsten hexacarbonyl.

5. The W having fast photochromic properties according to claim 3 18 O 49 The method for preparing a nano-based material is characterized in that: Step 1) The concentration of tungsten ions in the precursor solution is 0.005-0.030 mol / L.

6. The W having fast photochromic properties according to claim 1 or 2 18 O 49 Application of nanomaterials in erasable paper, anti-counterfeiting materials, smart windows, thermal insulation coatings, decorative materials, and packaging materials.

Citation Information

Patent Citations

  • Multi-morphology metal-doped W18O49 electrocatalyst and application thereof to hydrogen production by water electrolysis

    CN105749912A